United States--east coast, Georges Bank, western part : special chart for fishing industry / published at Washington, D.C. July 1934 by the U.S. Coast and Geodetic Survey, R.S. Patton, Director - U.S. Coast and Geodetic Survey (Washington, D.C. : United States Coast Survey, 1934)
Depths shown by isolines, gradient tints and soundings "Soundings in fathoms." "July 1934." "34-7/3." Includes radiobeacon signal guide and text Color 1:220,000